Direct oral anticoagulants compared to vitamin K-antagonists in patients with left ventricular thrombus. (3rd October 2022) - Seiler, T; Vasiliauskaite, E; Cioffi, G M; Madanchi, M; Attinger, A; Staempfli, S F; De Boeck, B; Kobza, R; Toggweiler, S; Moccetti, F; Wolfrum, M; Suter, Y; et al.
Abstract: Background/Introduction: In the setting of left ventricular thrombus (LVT), direct oral anticoagulants (DAOC) are poorly studied. Current European guidelines recommend treatment with Vitamin K antagonists (VKA) for 6 months. So far, several observational studies reported similar efficacity and safety of DOACs, compared to VKAs. Controversial findings were found in one big cohort, where higher stroke rates were reported among patients treated with DOAC compared to VKA, what raised concerns about the efficiency and safety to use DOACS in the setting of LVT. Purpose: This retrospective multicenter study compared thrombus resolution and clinical outcomes of patients with LVT treated with DOACs or VKAs. Methods: From an echocardiography database of three teaching hospitals in Switzerland, patients diagnosed with LVT between 2015 and 2021 were identified. All echocardiograms and outcomes were reviewed by independent physicians. Thrombus resolution rate and clinical outcomes were compared according to the underlying anticoagulation regimen. Results: Overall, 101 patients (17.8% females, mean age 63.3±13.2 years) were included. Among those, 50.5% had a recent myocardial infarction, 38.6% chronic ischemic heart disease and 10.9% suffered from non-ischemic cardiomyopathy. At hospital discharge, 48 (47.5%) were treated with DOACs and 53 (52.5%) with VKAs. Initial left ventricular ejection fraction was 38±13%. 93.1% patients presented with apical wall motion abnormalities, mean wall motion score index was 1.91±0.39. Initial thrombus size was comparable in both groups (table 1). Median follow-up was 799 (354; 1236) days and the clinical composite endpoint combining stroke, systemic embolism, bleedings, myocardial infarction and death was comparable in the VKA (22.6%) and DOAC (27.1%) group, respectively. There was no difference in major (4% vs. 6.3%) and minor (13.5% vs. 4.3%) bleeding events, neither for stroke and systemic thromboembolism (14.3% vs 14.9%) or death (11.3% vs 8.5%). Thrombus resolution rate after 1 year was similar in the VKA and DOAC group (75.5% vs. 76.7%), but early thrombus dissolution within the first month was faster in the VKA arm (p=0.049). In each group, 3 subjects had thrombus recurrence after cessation of anticoagulation. Conclusion: Among patients with LVT, DOACs appear to be a safe and effective alternative to vitamin K antagonists, but thrombus seems to dissolve slower in the first month. An adequately powered randomized trial is needed to confirm these findings. Funding Acknowledgement: Type of funding sources: None.